DOP061 Human amnion epithelial cells reduce intestinal inflammation in a 2, 4, 6-trinitrobenzene sulfonic acid induced model of acute colitis. (16th January 2018) - Kuk, N; Correia, J; Alhomrani, M; Lim, R; Sievert, W; Hodge, A; Moore, G
Abstract: Background: Patients with inflammatory bowel disease (IBD) experience diarrhoea, bleeding, abdominal pain and weight loss. The chronic nature of IBD requires lifelong immunosuppressive therapy with numerous associated side effects. Patients may become refractory to conventional therapy, necessitating surgical intervention. Research has focused on stem cells as a disease modifying and regenerative option. The pluripotent human amnion epithelial cell (hAEC) is an excellent candidate due to its plentiful and ethical supply from placentas, anti-inflammatory properties and no known safety issues. We examined the efficacy of hAECs in a 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) model of acute colitis. Methods: For pre-sensitisation of BALB/c mice, a 1.5 × 1.5 cm area of skin was shaved for administration of 1% (w/v) 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) in an acetone olive oil emulsion. Control mice received the same solution without TNBS. At Day 8, mice received a 150 µl enema of 2.5% TNBS (w/v) in 100% ethanol. Ethanol control mice received a 150 µl enema of absolute ethanol. At Day 9, TNBS-hAEC mice received an intravenous injection of 2 million hAECs. Control TNBS mice were untreated. Mice were monitored using the disease activity index (DAI) and culled at Day 12. Colitis severity was determined histologically through haematoxylin and eosin staining of the colon. IL-1β, TNF-α, IL-6, IFN-γ, IL-17, IL-23 were measured by ELISA. Neutrophil infiltration was evaluated by myeloperoxidase (MPO) activity assay. Results: Compared with untreated TNBS mice, bodyweight loss was significantly lower in hAEC-treated mice ( p < 0.0001) with an improved DAI ( p < 0.0001). In addition, hAEC treatment also prevented colon shortening by 17% ( p < 0.05) with a similar trend for colon weight ( p = 0.058). Histological severity scores were significantly higher in untreated TNBS mice compared with hAEC treated TNBS mice ( p < 0.05). Similarly, IL-1β, TNF-α, IL-6, IFN-γ, IL-17 and IL-23 were markedly lower in hAEC treated mice compared with untreated TNBS mice. MPO activity was lower in TNBS-hAEC mice compared with untreated TNBS mice. Conclusions: hAECs exerted therapeutic effects in a TNBS acute colitis model, modifying disease severity through reductions in neutrophil infiltration, pro-inflammatory and Th17-related cytokines. The protective nature of hAECs in colitis is promising and further research into this novel therapy is warranted.